Genomic instability: Crossing pathways at the origin of structural and numerical chromosome changes. (18th March 2015) - Russo, Antonella; Pacchierotti, Francesca; Cimini, Daniela; Ganem, Neil J.; Genescà, Anna; Natarajan, Adayapalam T.; Pavanello, Sofia; Valle, Giorgio; Degrassi, Francesca
<x xml:space="preserve">Abstract</x> Genomic instability leads to a wide spectrum of genetic changes, including single nucleotide mutations, structural chromosome alterations, and numerical chromosome changes. The accepted view on how these events are generated predicts that separate cellular mechanisms and genetic events explain the occurrence of these types of genetic variation. Recently, new findings have shed light on the complexity of the mechanisms leading to structural and numerical chromosome aberrations, their intertwining pathways, and their dynamic evolution, in somatic as well as in germ cells. In this review, we present a critical analysis of these recent discoveries in this area, with the aim to contribute to a deeper knowledge of the molecular networks leading to adverse outcomes in humans following exposure to environmental factors. The review illustrates how several technological advances, including DNA sequencing methods, bioinformatics, and live‐cell imaging approaches, have contributed to produce a renewed concept of the mechanisms causing genomic instability. Special attention is also given to the specific pathways causing genomic instability in mammalian germ cells. Remarkably, the same scenario emerged from some pioneering studies published in the 1980s to 1990s, when the evolution of polyploidy, the chromosomal effects of spindle poisons, the fate of micronuclei, were intuitively proposed to share mechanisms and pathways. Thus, an old working hypothesis has eventually found proper validation. Environ. Mol. Mutagen. 56:563–580, 2015. © 2015 Wiley Periodicals, Inc.